Avaliação da remoção de agrotóxicos por biorreator de membrana e pós-tratamentos de carvão ativado, osmose reversa e ozonização - Lopes , Thiago Santos de Almeida (2019)
The growing demand for food has generated a significant increase in the production and use of pesticides in various crops. These products tend to accumulate in the environment and thus cause several problems of environmental pollution and public health. Conventional systems of treatment of effluent are not efficient in the removal of these contaminants. For this reason, the objective of this work was to evaluate the potential of a membrane bioreactor (MBR) on a pilot scale, treating effluents from an industry of fruit processing, for the removal of toxic agrochemicals, individual forms and combined with other treatment technologies. The stability of the MBR was monitored by means of analyzes of COD, pH and TSS. The addition of pesticides occurred through the continuous insertion of stock solution to generate concentrations of 20 µg.L-1 of 2,4-D, carbendazim and diuron and 1.5 µg.L-1 of atrazine in the MBR. The determination of these compounds was performed by means of solid phase extraction (SPE) and liquid chromatography coupled to mass spectrometry (LC-MS/MS). The effectiveness of the MBR for removal of pesticides was evaluated by four experiments with variations of HDT and addition of powdered activated carbon (PAC) in the bioreactor, in addition to the operation of the post-treatment of activated carbon, reverse osmosis and ozonation. During the study, were executed chemical cleaning of the membranes with citric acid, sodium hydroxide, sodium hypochlorite and phosphoric acid. The bioreactor showed robustness and stability, to maintain the quality of the permeated even under high variations of cod from the raw effluent and the content of biomass in the silt. However, it provided only a partial removal of pesticides studied, emphasizing the need for a combined use with other treatment technologies for a complete removal. The introduction of CAP in the MBR promoted removals higher averages to 94% for carbendazim and diuron, however, the same efficacy was not obtained for 2,4-D and atrazine. Among the hybrid systems, formed by the union between MBR and postoperative treatments available in the pilot sewage treatment plant, the alternatives MBR/CAG adsorption and BRM/reverse osmosis generated excellent results, showing to be effective for the purposes of removal of pesticides. With respect to the MBR/ozonation system, it was observed a performance below to those listed above, but that can be explained by low levels of ozone applied.